Zung depression Scale: Psychometric Properties in human Immunodeficiency virus carriers - Del Águila Montoya, Luz Marina (2021)
Objective. To analyze the psychometric properties of the Zung depression scale in people with HIV in the department of San Martín. Methods. It was a basic and psychometric study, of non-experimental, cross-sectional, and instrumental design; the participants were 203 patients with HIV, of these (24.6% women, 35.5% men; 39.9% LGTBI) of these 56.7% do not know their viral load, and 50.7% do not follow treatment, the instrument applied was the Zung Depression Scale. Results. The items measure the depression variable together, through the CVC congruence of constructs was demonstrated obtaining a coefficient of .98, a bifactor model with adequate adjustment indices was proposed (X2= 273.2; df= 169; CFI= ,917; TLI= ,907; RMSEA=.055 and RMR=.056), similarly the reliability was high (a=.855; b=.869), in terms of normative data through the use of percentiles, measurement values of the scale were established according to the following criteria (low level 20- 32; moderate 33-48 and severe =>49). Conclusions. The scale has adequate psychometric properties for the evaluation of depression in patients with HIV.